Intrasellar schwannoma mimicking pituitary adenoma - Puduru, Sai Sudarsan (Indian Journal of Neurosurgery, 2013)
Intrasellar location of schwannoma is extremely uncommon and 18 cases are documented in the literature till now. This report describes intrasellar schwannoma in a patient in whom the neuroimaging features were suggestive of a pituitary adenoma.
Keywords: Intrasellar schwannoma; neuroimaging; pituitary adenoma